2013
DOI: 10.1115/1.4025793
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Three-Dimensional In Vivo Lumbar Intervertebral Joint Kinematics Using Dynamic Stereo-X-Ray Imaging

Abstract: Availability of accurate three-dimensional (3D) kinematics of lumbar vertebrae is necessary to understand normal and pathological biomechanics of the lumbar spine. Due to the technical challenges of imaging the lumbar spine motion in vivo, it has been difficult to obtain comprehensive, 3D lumbar kinematics during dynamic functional tasks. The present study demonstrates a recently developed technique to acquire true 3D lumbar vertebral kinematics, in vivo, during a functional load-lifting task. The technique us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…In particular, a fixed IAR does not permit translation, which has been reported in previous in vitro 30 and in vivo studies 31 . It may be that tension in the MLF constrains translation and if so this would have been obviated by use of a fixed IAR.…”
Section: Limitationsmentioning
confidence: 54%
“…In particular, a fixed IAR does not permit translation, which has been reported in previous in vitro 30 and in vivo studies 31 . It may be that tension in the MLF constrains translation and if so this would have been obviated by use of a fixed IAR.…”
Section: Limitationsmentioning
confidence: 54%
“…However, reported results regarding segmental contribution patterns have been inconsistent. Some studies have reported an increased contribution from caudal segments (L4-5, L5-S1) compared to the cephalic segments (Panjabi et al, 1994;Pearcy et al, 1984), others have reported a progressively decreasing contribution from cephalic to caudal segments (Li et al, 2009;Wong et al, 2004;Wong et al, 2006), while still others failed to detect significant differences in contributions (Aiyangar et al, 2014;Goel et al, 1985;Schultz et al, 1979;Tencer et al, 1982;Wu et al, 2014). Differences in experimental protocols do not completely account for these variations as the inconsistency persists even between studies using similar techniques.…”
Section: Introductionmentioning
confidence: 77%
“…Several studies have attempted to quantify segmental contributions to overall lumbar rotation. These include in vitro cadaveric studies (Goel et al, 1985;Miller et al, 1986;Schultz et al, 1979;Soni et al, 1982;Tencer et al, 1982), in vivo studies based on 2D lateral radiographs or static biplane radiography (Li et al, 2009;Passias et al, 2011;Pearcy et al, 1984;Plamondon et al, 1988), surface markerbased studies (Troke et al, 2001;Zhang and Xiong, 2003), uniplanar continuous radiography (Ahmadi et al, 2009;Harada et al, 2000;Kanayama et al, 1995;Okawa et al, 1998;Wong et al, 2004;Wong et al, 2006), and, more recently, dynamic biplane radiography (Aiyangar et al, 2014;Anderst et al, 2008;Wu et al, 2014). These studies have collectively and progressively improved our understanding of lumbar spinal motion.…”
Section: Introductionmentioning
confidence: 97%
“…To completely describe any spinal motion, 3D kinematics must be determined. Investigators have previously used biplanar fluoroscopy techniques to determine 3D spine kinematics [7,8,20,28]. This type of analysis more completely describes spinal motion but is very resource intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigators have used fluoroscopic methods to obtain 2D [17][18][19] and 3D [7,8,20] measurements of lumbar intervertebral motion. Although 3D measures of lumbar kinematics can provide highly detailed information about complex intervertebral kinematics, the technique requires sophisticated hardware and software for measuring images; such tools are not readily available in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%